"Broadbeam" irradiation of mammalian cells using a vertical microbeam facility. - Jeynes, J; Merchant, M; Barazzuol, L; Barry, M; Guest, D; Palitsin, V; Grime, G; Tullis, I; Barber, P; Vojnovic, B; Kirkby, K (2013)
A "broadbeam" facility is demonstrated for the vertical microbeam at Surrey's Ion Beam Centre, validating the new technique used by Barazzuol et al. (Radiat Res 177:651-662, 2012). Here, droplets with a diameter of about 4 mm of 15,000 mammalian cells in suspension were pipetted onto defined locations on a 42-mm-diameter cell dish with each droplet individually irradiated in "broadbeam" mode with 2 MeV protons and 4 MeV alpha particles and assayed for clonogenicity. This method enables multiple experimental data points to be rapidly collected from the same cell dish. Initially, the Surrey vertical beamline was designed for the targeted irradiation of single cells with single counted ions. Here, the benefits of both targeted single-cell and broadbeam irradiations being available at the same facility are discussed: in particular, high-throughput cell irradiation experiments can be conducted on the same system as time-intensive focused-beam experiments with the added benefits of fluorescent microscopy, cell recognition and time-lapse capabilities. The limitations of the system based on a 2 MV tandem accelerator are also discussed, including the uncertainties associated with particle Poisson counting statistics, spread of linear energy transfer in the nucleus and a timed dose delivery. These uncertainties are calculated with Monte Carlo methods. An analysis of how this uncertainty affects relative biological effect measurements is made and discussed.